Characterization and transmission of coconut cadang-cadang viroid variants in oil palm and coconut - Kanavedee, Raimathy (2016)
Coconut cadang-cadang viroid (CCCVd) is the causal agent of the devastating Coconut cadang-cadang disease in the Philippines. CCCVd variants have been associated with orange spotting (OS) disorder in Malaysian oil palm. The interrelation between characterized CCCVd variants and OS symptom variation as well as transmission of oil palm CCCVd variants into alternate host to observe the expression of symptoms that have not been studied in Malaysia. Characterization of CCCVd variants with OS and pathogenicity trials will enable better understanding of the disease epidemiology, viroid etiology and its transmission to alternate host. CCCVdlike RNAs from OS palms with symptom variation from different locations were extracted and characterized using an optimized and modified conventional Natrium Chloride EDTA Tris-HCL Mercaptoethanol (NETME) extraction method. The modification involved the inclusion of additional ethanol and lithium chloride precipitation stages thereby eliminating further purification through time-consuming non-denaturing Polyacrylamide Gel Electrophoresis (PAGE) process. Transmission study was carried out by inoculating CCCVdOP246 clones into 3 months old oil palm and coconut seedlings. The modified total nucleic acid extraction procedure proved to be successful and resulted in high quality RNA with consistent results in detection of CCCVd variants in oil palm. Characterized CCCVd variants from oil palm samples with variation in OS symptom (OPKS, OPBP and OPUP) showed 99% sequence similarity to CCCVdOP246 oil palm variant with substitution at positions at positions C104 > G, G105 > C and C140 > A (OSKS), C19 > G, and G35 > C (OSBP), and C24  U (OSUP) respectively. Transmission study found that CCCVd variant with 99% sequence similarity to CCCVdOP246 was detected in oil palm and coconut seedlings on the 3rd month and 6th month respectively after inoculation. Expression of orange spotting symptoms were observed on oil palm and coconut at the 6th month and 9th month respectively. CCCVd variants from palm with orange spotting symptom variation from different locations were successfully characterized. Variation in orange spotting symptom may be related to nucleotide change in the viroid sequence. Cross pathogenicity test of CCCVd variant into coconut were successful with viroid and symptom appearance.